Packaging Design Influence on Diagnostic Kit Identification Efficiency among Laboratory Users - Putri Merak Jingga Sameto (International Journal of Multidisciplinary Research of Higher Education, 2026)
Packaging design in diagnostic kits serves a dual function: safeguarding biologically sensitive components and facilitating rapid, accurate communication of technical information to laboratory personnel. This study investigates how visual elements specifically color schemes, typography, layout, and graphic symbols affect the ease of product identification among laboratory users. Using the Nusantics PathoScan hrHPV molecular diagnostic kit as a case study, the research adopts a qualitative descriptive approach through visual observation and formal product analysis. Findings reveal that consistent use of color coding enhances differentiation between kit components, while clear typographic hierarchy improves readability under time-sensitive laboratory conditions. Structured layout and standardized graphic symbols further support intuitive recognition, reducing the likelihood of misidentification. The study underscores the importance of packaging as a communication tool that extends beyond aesthetics, directly influencing laboratory workflow efficiency and diagnostic accuracy. Implications highlight the need for integrating principles of visual communication into biomedical product design, ensuring that packaging contributes to both functional safety and user-centered usability. This research provides insights for manufacturers, designers, and laboratory practitioners seeking to optimize diagnostic kit packaging for improved operational outcomes.